23c+5-2x=13x-51

Simple and best practice solution for 23c+5-2x=13x-51 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 23c+5-2x=13x-51 equation:


Simplifying
23c + 5 + -2x = 13x + -51

Reorder the terms:
5 + 23c + -2x = 13x + -51

Reorder the terms:
5 + 23c + -2x = -51 + 13x

Solving
5 + 23c + -2x = -51 + 13x

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-5' to each side of the equation.
5 + 23c + -5 + -2x = -51 + -5 + 13x

Reorder the terms:
5 + -5 + 23c + -2x = -51 + -5 + 13x

Combine like terms: 5 + -5 = 0
0 + 23c + -2x = -51 + -5 + 13x
23c + -2x = -51 + -5 + 13x

Combine like terms: -51 + -5 = -56
23c + -2x = -56 + 13x

Add '2x' to each side of the equation.
23c + -2x + 2x = -56 + 13x + 2x

Combine like terms: -2x + 2x = 0
23c + 0 = -56 + 13x + 2x
23c = -56 + 13x + 2x

Combine like terms: 13x + 2x = 15x
23c = -56 + 15x

Divide each side by '23'.
c = -2.434782609 + 0.652173913x

Simplifying
c = -2.434782609 + 0.652173913x

See similar equations:

| n(n-18)=-72 | | .1x+2.3=.7x+.5 | | 11x+y=10 | | 4(x-2)-2(x-4)=5(x+1)-3x | | 3x-8=5x+2 | | y=x^2+2x+1 | | x^2+8+10=0 | | 3x-15+2x=18+4x+25 | | (N-7)*4=32 | | (4y^2+6y-8)-(-9y+4)= | | 2+a=(2a-4) | | 10x+2=6x+3 | | x^18-y^21=0 | | 3x+5w=4 | | 2x+3=3x-1 | | 5(x-3)+18=28 | | (x+4)(2x+1)=4 | | 15-3n=6 | | 2(x-7)=5x+7 | | 2x+38=9x-18 | | 6x-9=39 | | -4x+2=-10 | | 8=5x+3+2x | | -2x-5=5 | | 3x+18=48-2x | | 4+6=12 | | x+4y=6v | | y=-2x^2+4x+3 | | 2x-10=22-2x | | 6(3a-4)+(3a+4)=5(a-2)-10 | | 5x-(-4x-1)=2 | | 2x+17=47-3x |

Equations solver categories